Role of mineralogy on the undrained monotonic simple shear response of compacted filtered copper tailings - Rodrigo Zorzal Velten; Carina Ulsen; João Paulo Rodrigues da Costa; Carlos Alex Alves Lima; Maiki Mafessoli; João Vítor de Azambuja Carvalho; Nilo Cesar Consoli (Soils and Foundations, 2025)
Tailings are anthropic materials whose behavior can be greatly affected by the mineralogy of their particles and the fabric formed. This paper focuses on the effects of tailings composition under plane strain conditions. For this, two copper tailings from distinct mines are studied. The tailings present a similar particle grading and morphology, so the main difference between them is restricted to mineralogy. Three compaction degrees and four effective confining pressure values (ranging from 50 to 400 kPa) were adopted. For the first time, the results of copper tailings under plane strain conditions are presented in the light of critical state soil mechanics due to the use of a simple shear apparatus equipped with backpressure and known horizontal stresses. The results revealed the influence of mineralogy on the critical state parameter M and the shape of the v – log p′ critical state lines. This highlights the importance of acknowledging mineralogy influence for properly designing tailings storage facilities.